Toxoplasma gondii and Neospora caninum infections in synanthropic rodents from Argentina - Dellarupe, Andrea (2019)
Toxoplasma gondii and Neospora caninum are closely related coccidian parasites (phylum Apicomplexa). This is the first study from urban synanthropic rodent species that involved serological and molecular diagnosis of T. gondii and N. caninum infection, and genotyping of T. gondii in Argentina. A total of 127 rodent samples were trap captured: Mus musculus (n = 78), Rattus norvegicus (n = 26) and Rattus rattus (n = 23). Antibodies against T. gondii and N. caninum were detected by IFAT in 32.8% (40/122) and 0.8% (1/122) of rodent samples, respectively, demonstrating contact with these protozoans. Additionally, T. gondii DNA was detected in 3.3% (4/123) of rodent central nervous system samples and 2 samples were genotyped by multilocus nPCR-RFLP. Neospora caninum DNA was not detected by PCR. The 2 genotyped samples were type III allele for all markers except for SAG-1 (type I for Rat1Arg and type II/III for Rat2Arg) and were identified as #48 and #2 (likely) according to the allele combinations reported on Toxo DB (Toxo-DB). The results of the present study revealed a wide distribution of T. gondii and less for N. caninum, in synanthropic rats and mice in the studied area.